2018
DOI: 10.1186/s13019-018-0710-0
|View full text |Cite
|
Sign up to set email alerts
|

Control angiography for perioperative myocardial Ischemia after coronary surgery: meta-analysis

Abstract: BackgroundPerioperative myocardial ischemia (PMI) in patients undergoing coronary artery bypass grafting (CABG) is associated with poor outcome. The aim of this study was to pool the available data on the outcome after control angiography and repeat revascularization in patients with perioperative myocardial ischemia (PMI) after coronary artery bypass grafting (CABG).MethodsA literature review was performed through PubMed, Scopus, ScienceDirect and Google Scholar to identify studies published since 1990 evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 11 publications
1
10
0
3
Order By: Relevance
“…Overall 30-day mortality in our study was comparable or even less than in recently published studies 2 8 10 19 20. In a recently published meta-analysis that included 1104 patients with perioperative MI after CABG, overall 30-day mortality was 8.9% 19. Furthermore, Preußer et al analysed mid-term results and reported survival rates at 7 years of 62.5% in the perioperative MI group and 81.1% in non-perioperative MI group 20…”
Section: Discussionsupporting
confidence: 78%
“…Overall 30-day mortality in our study was comparable or even less than in recently published studies 2 8 10 19 20. In a recently published meta-analysis that included 1104 patients with perioperative MI after CABG, overall 30-day mortality was 8.9% 19. Furthermore, Preußer et al analysed mid-term results and reported survival rates at 7 years of 62.5% in the perioperative MI group and 81.1% in non-perioperative MI group 20…”
Section: Discussionsupporting
confidence: 78%
“…Although control coronary angiography appears to be a valid life-savingÀguiding strategy for repeat revascularization in hemodynamically stable patients who develop a PMI after coronary artery bypass grafting, its safety and efficacy in terms of improving the short-and long-term outcomes of patients after noncardiac surgery should be determined in future studies. 12,13 The majority of responders (82%) also used clinical guidelines to reduce the rate of postoperative cardiovascular complications, although the quality of the majority of these recommendations was not strong. 10 The compelling evidence of the negative effect of PMI on short-and long-term morbidity and mortality after noncardiac surgery and the results of our survey suggest that several organizational steps should be undertaken in Russia.…”
Section: To the Editormentioning
confidence: 99%
“…Moreover, atherosclerosis remains a major cause of long-term morbidity and mortality worldwide as it is a prerequisite to a large number of cardiovascular diseases (CVDs) ( 2 ); for example, the prevalence of CVDs was predicted to reach 43.9% in the United States in 2030 ( 3 ), and in 2015 alone, 17.7 million people died from CVD worldwide ( 4 ). While a coronary artery bypass graft is widely performed for the revascularization of occluded vessels, it cannot be used to treat the damage caused by atherosclerosis ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…atherosclerosis is characterized by atherosclerotic plaques that result from inflammatory cell infiltration, lipid peroxidation, extracellular matrix deposition and other factors (1). Moreover, atherosclerosis remains a major cause of long-term morbidity and mortality worldwide as it is a prerequisite to a large number of cardiovascular diseases (cVds) (2); for example, the prevalence of cVds was predicted to reach 43.9% in the united States in 2030 (3), and in 2015 alone, 17.7 million people died from cVd worldwide (4).While a coronary artery bypass graft is widely performed for the revascularization of occluded vessels, it cannot be used to treat the damage caused by atherosclerosis (5). endothelial cell dysfunction is considered the main cause of atherosclerosis (6).…”
Section: Introductionmentioning
confidence: 99%